The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1038/ejhg.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

Reduced transcript expression of genes affected by inherited and de novo CNVs in autism

Abstract: Individuals with autism are more likely to carry rare inherited and de novo copy number variants (CNVs). However, further research is needed to establish which CNVs are causal and the mechanisms by which these CNVs influence autism. We examined genomic DNA of children with autism (N¼41) and healthy controls (N¼367) for rare CNVs using a high-resolution array comparative genomic hybridization platform. We show that individuals with autism are more likely to harbor rare CNVs as small as B10 kb, a threshold not p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 28 publications
(27 reference statements)
6
71
1
2
Order By: Relevance
“…There were no additional CNV calls in any of the family members, which strongly suggests a modifier of unknown origin as previously reported in thrombocytopenia-absent radius syndrome (OMIM 274000) [Klopocki et al, 2007]. There may be a smaller CNV occurring elsewhere in the genome, below the resolution detected by Affymetrix arrays, and conferring a transcription-related, neurodevelopmental or receptor function that exacerbates the effect of the 17q12 deletion in the offspring [Nord et al, 2011]. Alternatively, there may be a relatively common variant or polymorphism which acts as trigger.…”
Section: Discussionsupporting
confidence: 69%
“…There were no additional CNV calls in any of the family members, which strongly suggests a modifier of unknown origin as previously reported in thrombocytopenia-absent radius syndrome (OMIM 274000) [Klopocki et al, 2007]. There may be a smaller CNV occurring elsewhere in the genome, below the resolution detected by Affymetrix arrays, and conferring a transcription-related, neurodevelopmental or receptor function that exacerbates the effect of the 17q12 deletion in the offspring [Nord et al, 2011]. Alternatively, there may be a relatively common variant or polymorphism which acts as trigger.…”
Section: Discussionsupporting
confidence: 69%
“…20 Finally, an autistic patient was identified carrying a deletion of an putative upstream promoter region, which resulted in reduced expression levels. 21 Thus, although these deletions do not interrupt the protein product, they may affect regulatory elements to produce altered functional levels of CNTNAP2.…”
Section: Cntnap2 and Cognitive Disorders Mutations Of Cntnap2mentioning
confidence: 99%
“…More recently, we have found that loss of GluD1 produces molecular phenotypes relevant to autism and developmental delay, including impaired dendritic spine pruning and switch in N-methyl-D-aspartate (NMDA) receptor GluN2B to the GluN2A subunit in the hippocampus and prefrontal cortex (Grossman et al, 2006;Penzes et al, 2011;Swanger et al, 2011;Gupta et al, 2015). Indeed, singlenucleotide polymorphism and copy-number variation studies have identified the GRID1 gene, which codes for GluD1, as a susceptibility gene for autism, schizophrenia, bipolar disorder, and major depression (Fallin et al, 2005;Glessner et al, 2009;Smith et al, 2009;Greenwood et al, 2011;Nord et al, 2011;Edwards et al, 2012;Griswold et al, 2012).…”
Section: Introductionmentioning
confidence: 99%